2008
DOI: 10.1080/03009740701774941
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of bone morphogenetic proteins to disease activity and radiographic damage in patients with ankylosing spondylitis

Abstract: Overproduction of BMP-2 and BMP-7 was noted in AS patients, and serum BMP-7 levels reflected radiographic damage observed in AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 12 publications
4
35
0
Order By: Relevance
“…Serum levels of BMP-2 and BMP-7 were elevated in AS patients, and BMP-7 correlated with radiographic change after a mean follow-up of 51.7 months [46].…”
Section: Biomarkers For Disease Prognosismentioning
confidence: 88%
“…Serum levels of BMP-2 and BMP-7 were elevated in AS patients, and BMP-7 correlated with radiographic change after a mean follow-up of 51.7 months [46].…”
Section: Biomarkers For Disease Prognosismentioning
confidence: 88%
“…These results indicated that BQZ may affect the osteogenic differentiation of fibroblasts by regulating Cx43. Overproduction of BMP-2 was noted in AS patients (30). BMP-2 is secreted mainly by osteoblasts, and the high levels of BMP-2 is AS patients may lead to new bone formation by stimulating the osteogenic differentiation of fibroblasts (31).…”
Section: Discussionmentioning
confidence: 99%
“…], for example, MMP3 is significantly associated with this endpoint and it is now under further evaluation 54,55,56,57,58 . Among imaging techniques, ultrasound was considered an interesting candidate for assessing SpA enthesitis as a marker of inflammatory activity both at site specific (entheses) and patient levels 59,60,61,62,63 .…”
Section: Journal Of Rheumatologymentioning
confidence: 99%